Micro-to-nano scale filling behavior of PMMA during imprinting - Jingmin Li (Nature Portfolio, 2017)
Abstract The filling behavior of polymers in narrow gaps or small pores is important for the dynamics of polymeric micro/nanostructure fabrication. Here, the filling behavior, the mechanical properties, and the stress versus strain relationship of 996 kD poly (methyl methacrylate) (PMMA) at a scale from micron to molecular confinement are measured. It has been found that the solid polymer exhibits elastic-plastic dominant deformation behavior at micron scale. As the scale reduces to submicron, the resistance to deformation of the polymeric solid has a pronounced reduction. A softening effect and the visco-dominant behavior which is always exhibited by melt flow is observed. In confinement conditions, an anomalous hardening effect is found. The modulus and the hardness of 996 kD PMMA have been found to increase dramatically. The stress-strain curve also exhibits an obvious hardening phenomenon which is contrary to the conventional shear thinning and deformation acceleration results. The results of this paper show that the PMMA can exhibit a change of “solid-fluid-solid” in mechanical character at micron to molecular confinement scale.